2020
DOI: 10.1016/j.psj.2019.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural extracts obtained from food industry by-products on nutritional quality and shelf life of chicken nuggets enriched with organic Zn and Se provided in broiler diet

Abstract: This study investigated the influence of an organic mineral-supplemented broiler diet on the quality of nuggets. The resulting chicken nuggets were enriched with inorganic and organic forms of Zn and Se. The nuggets were processed by incorporating extracts from food industry by-products ( rosemary [R H and R L ], hydroxytyrosol [ HYT ], pomegranate [ P ], grape [ GS ], and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Protein oxidation was measured in relation to the thiol concentration. The concentration of the thiol groups was determined after derivatisation by Ellman’s reagent, 5,5-dithiobis (2-nitrobenzoic acid) (DTNB) [ 25 ], following the method described by Martínez, Ros, and Nieto (2020) [ 26 ]. The absorbance was spectrophotometrically measured at 412 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Protein oxidation was measured in relation to the thiol concentration. The concentration of the thiol groups was determined after derivatisation by Ellman’s reagent, 5,5-dithiobis (2-nitrobenzoic acid) (DTNB) [ 25 ], following the method described by Martínez, Ros, and Nieto (2020) [ 26 ]. The absorbance was spectrophotometrically measured at 412 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The samples could be ranged in the following order of increasing SH group content: Control < nutmeg < cardamom ≈ caraway < bay leaf < black seed < allspice ≤ cloves. Increased oxidative stability of proteins after addition of plant extracts was reported in chicken nuggets stored at −18 • C containing grape seed extract [43], and in raw pork patties with persimmon peel extract [38]. Whereas, in chicken sausages with hydroxytyrosol extract the SH content was lower than in the control sample, which was probably due to protein-phenol interactions [29].…”
Section: Protein Oxidationmentioning
confidence: 96%
“…The loss of SH groups, which is a consequence of disulfide formation, has been often used as the marker of protein oxidation [29,38,43]. Based on the results, it could be stated that both, time and the treatments affected significantly the content of SH groups (Figure 4).…”
Section: Protein Oxidationmentioning
confidence: 97%
“…Other studies have investigated whether the addition of natural extract containing phenolic compounds or inclusion of rosemary or thyme leaves in the diet of pregnant ewes has an influence on the oxidative stability and sensory properties of raw and cooked lamb, poultry, as well as pork and chicken meat [125][126][127][128][129][130][131][132][133][134][135][136]. In one of these studies, the authors reported that the inclusion of thyme in the diet of ewes favored a high antioxidant capacity in samples of lamb meat.…”
Section: Incorporation Of Thyme In Meatmentioning
confidence: 99%